Histopathology Image Analysis in Two Long-Term Animal Experiments with Helical Flow Total Artificial Heart - Wotke, Jiri; Homolka, Pavel; Vasku, Jaromír; Dobsak, Petr; Palanova, Petra; Mrkvicova, Veronika; Konecny, Petr; Soska, Vladimir; Pohanka, Michal; Novakova, Marie; Yurimoto, Terumi; Saito, Itsuro; et al. (Artificial organs, 2016)
Histopathological analysis can provide important information in long-term experiments with total artificial heart (TAH). Recently, a new type of blood pump, the helical flow total artificial heart (HF-TAH) was developed. This study aimed to investigate the changes in selected vital organs in animal experiments with implanted HF-TAH. Samples from lung, liver, and kidneys from two female goats (No. 1301 and No. 1304) with implanted HF-TAH were analyzed. Tissue samples were fixed in 10% formaldehyde and 4 µm thick transverse sections were stained with hematoxylin-eosin (HE). Additional staining was done for detection of connective tissue (Masson-Goldner stain) and for detection of iron (hemosiderin) deposits (Perls stain). Sections were scanned at 100× and 500× magnification with a light microscope. Experiment no. 1301 survived 100 days (cause of termination was heavy damage of the right pump); experimental goat no.1304 survived 68 days and was sacrificed due to severe right hydrodynamic bearing malfunction. Histopathological analysis of liver samples proved signs of chronic venostasis with limited focal necrotic zones. Dilated tubules, proteinaceous material in tubular lumen, and hemosiderin deposits were detected in kidney samples. Contamination of the organs by embolized micro-particles was suspected at the autopsy after discovery of visible damage (scratches) of the pump impeller surface (made from titanium alloy) in both experiments. Sporadic deposits of foreign micro-particles (presumably titanium) were observed in most of the analyzed parenchymal organs. However, the described deposits were not in direct connection with inflammatory reactions in the analyzed tissues. Histopathological analysis showed the presence of minimal contamination of the lung, kidney, and liver tissue samples by foreign material (titanium very likely). The analysis showed only limited pathological changes, especially in liver and kidneys, which might be attributed to the influence of artificial perfusion often observed in chronic TAH experiments.
Keywords: Liver; Animals; Kidney; Female; Goats; Lung; Prosthesis Design; játra; Prosthesis Implantation; protézy - design; ženské pohlaví; Heart, Artificial; Microparticles; implantace protézy; Titanium; Histopathology; umělé srdce; titan; Titanium alloy; kozy; Total artificial heart; plíce; zvířata; ledviny; Helical flow